HUBUNGAN DUKUNGAN KELUARGA TERHADAP PENYESUAIAN DIRI PADA PASIEN PSIKOTIK RESOSIALISASI DI PANTI SOSIAL BINA LARAS PHALA MARTHA SUKABUMI - Desi Mediawati; Bambang Syamsul Arifin; Tintin Supriyatin (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2012)
This research aims to obtain empirical data about correlation between family support and self-adaptation among resocialization psychotic patients in Panti Sosial Bina Laras Phala Martha Sukabumi. Subjects are 41 psychotic patients in resocialization phase in Panti Sosial Bina Laras Phala Martha Sukabumi. Result shows that there is positive correlation between family support with self-adaptation among psychotic patients in Panti Bina Laras Phala Martha Sukabumi. In conclusion, high support from family will make high self adaptation while if adaptation is low then the family support must be low.